Improving the diagnosis of central nervous system infections in adults through introduction of a simple lumbar puncture pack. Issue 5 (15th June 2012) - Michael, Benedict Daniel; Powell, Graham; Curtis, Sarah; Bailey, Lisa; Almond, Solomon; McGill, Fiona; Cousins, David; Hart, Ian J; Griffiths, Michael; Kneen, Rachel; Solomon, Tom
Abstract : Background: Acute central nervous system (CNS) infections, such as meningitis and encephalitis, are neurological emergencies for which accurate diagnosis and prompt treatment improve the outcome. Analysis of the cerebrospinal fluid (CSF) obtained at lumbar puncture (LP) is pivotal to establishing the diagnosis and guiding management. PCR analysis of the CSF is an important method to identify the pathogen. However, recent studies have demonstrated that many patients have inadequate CSF sample collection and analysis. Aims: To increase the proportion of patients having an LP for a suspected CNS infection for whom the appropriate samples are taken. Secondary aims included to increase the proportion of patients for whom a pathogen was identified. Methods: The authors developed an LP pack for patients with a suspected CNS infection. They also assessed its impact on diagnosis by comparing practice 6 months before and after its introduction to the medical admissions unit of a large inner city teaching hospital. Results: The authors found that the LP pack reduced major errors in CSF sample collection and improved the diagnosis of acute CNS infections; among those patients who had a CSF pleocytosis, the proportion with a viral or bacterial pathogen identified by PCR was increased after introduction of the pack. Discussion: This study has demonstrated that the introduction of a simple low-cost LP pack into a busy acute medical setting can improve the diagnosis of CNS infections and, thus, guide treatment. Further work is needed to see if these results are more widely reproducible, and to examine the clinical, health and economic impact on overall management of patients with suspected CNS infections.